White rust species (Chromista, Peronosporomycetes, Albuginales, Albuginaceae) on common weeds in Hungary - Tóth, Tamás; Kövics, György (Acta Agraria Debreceniensis, 2015)
The obligate plant parasite fungi in the family Albuginaceae are responsible for causing white rust diseases on weeds and they are rather common worldwide. Weedy plants with characteristic symptoms have been collected in 2014 and 2015 on location Hajdú-Bihar and Jász-Nagykun-Szolnok counties in Hungary. The determination of the species were based on the morphological characters both pathogens and hosts. Albugo candida was determined on shepherd’s purse (Capsella bursa-pastoris). Common purslane (Portulaca oleracea) is a host for Wilsoniana portulacae. The fungus Wilsonia bliti (syn.: Albugo bliti), the causal agent of white rust disease was found on redroot pigweed (Amaranthus retroflexus).